Effects of Renal Denervation on Sympathetic Activation, Blood Pressure, and Glucose Metabolism in Patients with Resistant Hypertension - Schlaich, Markus P.; Hering, Dagmara; Sobotka, Paul A.; Krum, Henry; Lambert, Gavin W.; Lambert, Elisabeth A.; Esler, Murray D. (Frontiers in Physiology, 2012)
Increased central sympathetic drive is a hallmark of several important clinical conditions including essential hypertension, heart failure, chronic kidney disease, and insulin resistance. Afferent signaling from the kidneys has been identified as an important contributor to elevated central sympathetic drive and increased sympathetic outflow to the kidney and other organs is crucially involved in cardiovascular control. While the resultant effects on renal hemodynamic parameters, sodium and water retention, and renin release are particularly relevant for both acute and long term regulation of blood pressure, increased sympathetic outflow to other vascular beds may facilitate further adverse consequences of sustained sympathetic activation such as insulin resistance, which is commonly associated with hypertension. Recent clinical studies using catheter-based radiofrequency ablation technology to achieve functional renal denervation in patients with resistant hypertension have identified the renal nerves as therapeutic target and have helped to further expose the sympathetic link between hypertension and insulin resistance. Initial data from two clinical trials and several smaller mechanistic clinical studies indicate that this novel approach may indeed provide a safe and effective treatment alternative for resistant hypertension and some of its adverse consequences.